On Stability of Integral Sets of Impulsive Differential Systems - Perestyuk, N. A.; Chernikova, O. S. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We introduce the notion of stability of integral sets of impulsive differential systems of general form (with nonfixed times of impulse influence). We establish conditions sufficient for the stability of an integral set.